1984
DOI: 10.2307/3053447
|View full text |Cite
|
Sign up to set email alerts
|

The Oven Bird's Song: Insiders, Outsiders, and Personal Injuries in an American Community

Abstract: It is not an exaggeration to say that we live in an era preoccupied with the problems and challenges of obtaining justice in civil cases. Concerns expressed about the civil justice system range from warnings that civil court dockets are clogged by disputants too litigious for their own good to complaints that the legal system is used too rarely in civil cases. The authors approach their analysis with a sense that this subject area is in need of more and better theory. It is an unfortunate fact that discussions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(76 citation statements)
references
References 2 publications
6
70
0
Order By: Relevance
“…1982; Salamon and Tornatore, 1994), and values and norms (Engel, 1984;Spain, 1993). Previous studies also suggest that willingness to pay for improved environmental amenities is a function of household characteristics and location (e.g., Breffle et al, 1998).…”
Section: The Heckit Modelmentioning
confidence: 93%
See 1 more Smart Citation
“…1982; Salamon and Tornatore, 1994), and values and norms (Engel, 1984;Spain, 1993). Previous studies also suggest that willingness to pay for improved environmental amenities is a function of household characteristics and location (e.g., Breffle et al, 1998).…”
Section: The Heckit Modelmentioning
confidence: 93%
“…Perceptions have been investigated with respect to resident's and homeowner's characteristics, including length of time of residence (Baldassare, 1986;Myers, 1989;Doherty, 1987), social class or income (Lovejoy et al, 1982;Salamon and Tornatore, 1994), and values and norms (Engel, 1984;Spain, 1993). However, these studies examine the impact of the respective characteristics on perceptions independently, even though all of these characteristics are found to have significant influences on perceptions about land-use policy.…”
mentioning
confidence: 96%
“…Black contends that law is used less frequently among intimates than among strangers, and more frequently as the social distance between people increases. For example, Engel (1999) found that residents of a small community are reluctant to sue one another, even in the case of serious injuries. When residents do sue, he found that the parties are separated by a significant degree of relational distance.…”
Section: Morphologymentioning
confidence: 97%
“…Studying both aspects of legal environments is important because, as LoPucki demonstrated, even in communities with the same written laws there can be "persistent, systematic differences in legal outcomes" (1996,1502) due to differences in interpretation, expectations, social norms, and attitudes. In fact, this is one of the central findings in the sociology of law: The interpretation of law by legal and non-legal actors can have profound implications for both the making of law and legal outcomes (see, for example, Edelman 1990Edelman , 1992Suchman 1997, 1999;Engel 1984;Sutton et al 1994). In other words, while written laws shape what is legally viable, it is the law "in people's heads" that shapes how law is applied and carried out.…”
Section: Legal Decision Making In Contextmentioning
confidence: 95%